#### Answer

$6 \pi r^2$.

#### Work Step by Step

$2 \pi r^2 + 2 \pi r \cdot 2 r = 2 \pi r^2 + 4 \pi r^2 = (2 + 4) \pi r^2 = 6 \pi r^2 $.

Published by
Wiley

ISBN 10:
1118583191

ISBN 13:
978-1-11858-319-7

$6 \pi r^2$.

$2 \pi r^2 + 2 \pi r \cdot 2 r = 2 \pi r^2 + 4 \pi r^2 = (2 + 4) \pi r^2 = 6 \pi r^2 $.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.